1989
DOI: 10.2307/3577633
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Combined Mortality Data on Workers at the Hanford Site, Oak Ridge National Laboratory, and Rocky Flats Nuclear Weapons Plant

Abstract: An important objective of studies of workers exposed occupationally to chronic low doses of ionizing radiation is to provide a direct assessment of health risks resulting from this exposure. This objective is most effectively accomplished by conducting combined analyses that allow evaluation of the totality of evidence from all study populations. In this paper, combined analyses of mortality in workers at the Hanford Site, Oak Ridge National Laboratory, and Rocky Flats Nuclear Weapons Plant are presented. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
2

Year Published

1990
1990
2000
2000

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 14 publications
5
31
0
2
Order By: Relevance
“…Their SMR values for all causes (SMR 0.74), all cancers (SMR 0.53), and circulatory diseases (SMR 0.66) were all significantly below those of the general US female population. These low SMR values were generally consistent with results reported in other studies of workers who have been exposed occupationally to low levels of external radiation (23,(26)(27)(28)(33)(34). The healthy worker effect might be one of the reasons for the low SMR values.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Their SMR values for all causes (SMR 0.74), all cancers (SMR 0.53), and circulatory diseases (SMR 0.66) were all significantly below those of the general US female population. These low SMR values were generally consistent with results reported in other studies of workers who have been exposed occupationally to low levels of external radiation (23,(26)(27)(28)(33)(34). The healthy worker effect might be one of the reasons for the low SMR values.…”
Section: Discussionsupporting
confidence: 81%
“…The SMR values for cancers of the stomach, rectum, bone, prostate, lymphosarcoma, and Hodgkin's disease were all greater than one , but none of them was statistically significant. By combining mortality data on workers at the Hanford Site, Oak Ridge National Laboratory, and Rocky Flats Nuclear Weapons Plant, Gilbert et al (33) found no evidence of a correlation between radiation exposure and mortality from all cancers or from leukemia. Of the 11 other specific types of cancers analyzed, they found that multiple myeloma was the only cancer with a statistically significant correlation with radiation exposure .…”
Section: Discussionmentioning
confidence: 99%
“…The statistical power of individual studies was, however, low and in most cohorts the confidence intervals of the risk estimates were compatible with a range of possibilities, from negative effects to risks an order of magnitude greater than those on which current radiation protection recommendations are based. Combined analyses of data from some of these studies have therefore been carried out at the national and international levels (4,5,(55)(56)(57) specifically to test the adequacy of existing risk extrapolations. Table 2 presents the results of the International Agency for Research on Cancer (IARC) international combined analyses (5), carried out on 96,000 workers, and compares them to estimates obtained from IARC reanalyses of the atomic bomb survivors data.…”
Section: Resultsmentioning
confidence: 99%
“…For radiosensitive tissues, particularly multiple myeloma and leukemia, only multiple myeloma was consistently associated with low level radiation at Hanford (3,5,(7)(8)(9)(11)(12)(13). In the trend tests multiple myeloma continually showed a positive trend, or increases in mortality with increased exposure.…”
Section: Trend Testmentioning
confidence: 99%